2022
DOI: 10.1371/journal.ppat.1010774
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and consequences of the HTLV-1 proviral plus-strand burst

Abstract: Expression of the transcriptional transactivator protein Tax, encoded on the proviral plus-strand of human T-cell leukaemia virus type 1 (HTLV-1), is crucial for the replication of the virus, but Tax-expressing cells are rarely detected in fresh blood ex vivo. The dynamics and consequences of the proviral plus-strand transcriptional burst remain insufficiently characterised. We combined time-lapse live-cell imaging, single-cell tracking and mathematical modelling to study the dynamics of Tax expression at sing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…To exclude the possibility that the anti-Tax antibody used in intracellular staining altered chromatin looping, we performed q4C assays using T-cell clones transduced with a reporter construct which expresses a modified EGFP with a half-life of ~2h (d2EGFP-TBX4B) when stimulated by Tax protein [ 11 ]. The GFP signal intensity was positively correlated with Tax expression [ 12 ]. Provirus-expressing (GFP + ) cells and non-expressing (GFP − ) cells were flow-sorted after fixation in 1% paraformaldehyde and subjected to the q4C assay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To exclude the possibility that the anti-Tax antibody used in intracellular staining altered chromatin looping, we performed q4C assays using T-cell clones transduced with a reporter construct which expresses a modified EGFP with a half-life of ~2h (d2EGFP-TBX4B) when stimulated by Tax protein [ 11 ]. The GFP signal intensity was positively correlated with Tax expression [ 12 ]. Provirus-expressing (GFP + ) cells and non-expressing (GFP − ) cells were flow-sorted after fixation in 1% paraformaldehyde and subjected to the q4C assay.…”
Section: Resultsmentioning
confidence: 99%
“…While the transcriptional burst of tax is short-lived, Tax protein persists for some days in each cell. In the present experiment, the cells were selected on the basis of Tax protein expression: at any one time, therefore, the percentage of Tax protein-positive cells at any instant in these clones in vitro is relatively high [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To exclude the possibility that the anti-Tax antibody used in intracellular staining altered chromatin looping, we performed q4C assays using Tcell clones transduced with a reporter construct which expresses a modified EGFP with a half-life of ~2h (d2EGFP-TBX4B) when stimulated by Tax protein [11]. The GFP signal intensity was positively correlated with Tax expression [12]. Provirus-expressing (GFP + ) cells and non-expressing (GFP − ) cells were flow-sorted after fixation in 1% Next, we asked whether the aberrant host transcription is associated with proviral transcription or simply with the presence of the provirus, regardless of transcription.…”
Section: Htlv-1 Expression Proviral Plus-strand Expression Reduces Ch...mentioning
confidence: 99%
“…At the onset of ATL, approximately 50% of cases do not show Tax expression due to methylation or deletion of the 5′ LTR region; thus, selective proliferation of clones that are not attacked by CTLs is likely to be promoted [22]. In addition, recent studies have revealed that sense-side transcription leading to Tax expression occurs in transient bursts even in the absence of genomic deletions or epigenetic changes in the provirus [23][24][25]. This may be a viral survival strategy that minimizes Tax expression and avoids CTL attacks.…”
Section: Introductionmentioning
confidence: 99%